Development of Burnout in Physical Therapist Students and Associated Factors: A Study During COVID-19. Issue 3 (12th September 2022) - Smith, Allison; Ellison, Jennifer; Bogardus, Jennifer; Gleeson, Peggy
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Burnout is a negative response to work-related stress and follows a developmental process that might begin during students' academic studies. Review of Literature: Numerous factors affect burnout in graduate students, and few published studies have assessed burnout in physical therapist students. Subjects: Participants included 1, 340 Doctor of Physical Therapy (DPT) students from DPT programs across the United States. Method: Students completed a Psychdata survey in fall 2020 that assessed burnout using the Oldenburg Burnout Inventory for Students (OLBI-S), resilience using the Connor-Davidson Resilience Scale (CD-RISC), perceived stress using the Perceived Stress Scale (PSS), and additional questions regarding levels of support and the learning environment. Burnout levels for each year in a DPT program were determined using 2 one-way independent analysis of variances, 1 for each OLBI-S subscale. Cutoff scores to group students into the burnout and nonburnout groups were determined using quartiles. Logistic regression was used to identify factors that may have an influence on the development of burnout. Results: No significant difference was found in burnout scores among students in different years in a DPT program. Using cutoff scores, 35.4% of DPT students were in the burnout group. Factors found to be statistically significant in predicting burnout were satisfaction with the level of support from faculty, satisfaction with overall learning environment, CD-RISC score, and PSS score (χ 2 (4) = 266.827, P < .001). The final model explained 24.8% of the variance and correctly classified 72.1% of cases. Discussion and Conclusion: Students who have higher levels of perceived stress, lower levels of satisfaction with the level of support from faculty, and lower levels of satisfaction with their overall learning environment at DPT school may be more likely to develop burnout, while students who have higher levels of resilience may be less likely to develop burnout. This study was conducted during the COVID-19 pandemic and may not be generalizable to nonpandemic times.